Simple Global Path Planning Algorithm Using a Ray-Casting and Tracking Method - Kim, In Seok; Lee, Woong Ki; Hong, Young Dae (Journal of Intelligent and Robotic Systems: Theory and Applications, 2018)
This paper proposes a simple global path planning algorithm using a ray’s feature of straight in nature with a random reflection model. The ray-casting and tracking (RCT) method is designed to solve global single-query path planning problems with fast convergence time. It is a random sampling-based algorithm that reflects rays with the maximum search length, which is a line of sight restricted only by the obstacles blocking the rays. RCT guarantees a competent path that follows an obstacle’s edges like a path generated by a visibility graph (VG). We demonstrated RCT’s superior performance in terms of both convergence time and path length on various environments that have their own features compared to other well-known path planning algorithms such as the A*, rapidly-exploring random trees, and VG.
Keywords: Convergence time; Global path planning; Path-planning algorithm; Random reflections; Rapidly-exploring random trees; Ray casting; Sampling-based; Visibility graphs; Navigation of mobile robots; Nondeterministic global path planning; Ray-casting and tracking; Sampling-based path planning